Makna Naketi dalam Pandangan Masyarakat Dawan: Kajian Berperspektif Pastoral - Benu, Wasti Juningsi (UI Scholars Hub, 2022)
This research aims to describe and analyze the meaning of naketi in the view of the Dawan community in Soe City. This research is motivated by the fact that Dawan people tend to practice naketi to overcome the crisis or ongoing problems experienced. The study employs descriptive research methods with qualitative approaches. Data collection uses interview methods and library studies. The data is analyzed using a pastoral theory of meaning and function. The results of the analysis show that the practice of naketi is a form functioning as pastoral counseling based on Dawan community culture. Naketi, in the view of the Dawan community, is a method, effort, and way for them to organize, align, correct and purify themselves from the violation of the sins they committed, destroying their system or order of life. Therefore, naketi’s practice aims to improve and solve various ongoing crises experienced. There are religious, social, and moral values in the meaning and practice of naketi carried out by the Dawan community.